2020
DOI: 10.1083/jcb.202001003
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic phosphorylation of Pex14p regulates peroxisomal import machinery

Abstract: Peroxisomal matrix proteins are imported into peroxisomes via membrane-bound docking/translocation machinery. One central component of this machinery is Pex14p, a peroxisomal membrane protein involved in the docking of Pex5p, the receptor for peroxisome targeting signal type 1 (PTS1). Studies in several yeast species have shown that Pex14p is phosphorylated in vivo, whereas no function has been assigned to Pex14p phosphorylation in yeast and mammalian cells. Here, we investigated peroxisomal protein import and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Many peroxisomal proteins, involved in various processes such as peroxisome biogenesis and protein import, are phosphorylated according to phospho-proteomics studies, but the biological function of this phosphorylation remains largely unknown in mammals ( Oeljeklaus et al, 2016 ). Phosphorylation of human PEX5, the shuttling import receptor for peroxisomal matrix proteins, has been shown to be implicated in pexophagy in response to reactive oxygen species ( Zhang et al, 2015 ), while phosphorylation of PEX14, a part of the peroxisomal import machinery, suppressed the import of catalase into peroxisomes under oxidative stress conditions and in mitotic cells ( Okumoto et al, 2020 ; Yamashita et al, 2020 ). Our novel findings on the regulation of the ACBD5-VAPB tether, and subsequent peroxisome–ER membrane contacts, represent another example for a physiologic role of phosphorylation of peroxisomal membrane proteins in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Many peroxisomal proteins, involved in various processes such as peroxisome biogenesis and protein import, are phosphorylated according to phospho-proteomics studies, but the biological function of this phosphorylation remains largely unknown in mammals ( Oeljeklaus et al, 2016 ). Phosphorylation of human PEX5, the shuttling import receptor for peroxisomal matrix proteins, has been shown to be implicated in pexophagy in response to reactive oxygen species ( Zhang et al, 2015 ), while phosphorylation of PEX14, a part of the peroxisomal import machinery, suppressed the import of catalase into peroxisomes under oxidative stress conditions and in mitotic cells ( Okumoto et al, 2020 ; Yamashita et al, 2020 ). Our novel findings on the regulation of the ACBD5-VAPB tether, and subsequent peroxisome–ER membrane contacts, represent another example for a physiologic role of phosphorylation of peroxisomal membrane proteins in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have also identified Ser 266 and Ser 313 residues of S. cerevisiae Pex14 to be phosphorylated (Albuquerque et al, 2008). H 2 O 2 -induced phosphorylation of Pex14 at Ser 232 was reported in mammalian cells recently, and this PTM suppressed the peroxisomal import of catalase in mammalian mitotic cells (Okumoto et al, 2020;Yamashita et al, 2020).…”
Section: Pex14mentioning
confidence: 82%
“…Phosphorylation of human PEX5, the shuttling import receptor for peroxisomal matrix proteins, has been shown to be implicated in pexophagy in response to ROS (Zhang et al, 2015). Phosphorylation of mammalian PEX14, a membrane protein that is part of the peroxisomal import machinery, suppressed the import of catalase into peroxisomes under oxidative stress conditions and in mitotic cells (Okumoto et al, 2020;Yamashita et al, 2020). Additionally, Pex14p phosphorylation in the yeast S. cerevisiae controls the import of Cit2p, the peroxisomal isoform of citrate synthase (Schummer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%